The effects of incremental ulnar styloid osteotomies on distal radioulnar joint stability: a biomechanical cadaveric study. (June 2019) - Cheema, Adnan N.; Dardas, Agnes Z.; Hast, Michael W.; Gray, Benjamin L.
The purpose of this study was to systematically quantify distal radioulnar joint stability with a cadaveric model, using radiographic and joint contact force measurements. Six fresh-frozen cadavers underwent sequential ulnar styloid osteotomies. Posteroanterior and lateral stress radiographs were obtained and joint contact forces and areas were measured. Posteroanterior radiographs showed a significant increase in the distal radioulnar joint gap after osteotomy of the base of the ulnar styloid. Contact force and contact area measurements were not significantly different. We conclude that fractures that involve the ulnar styloid base should be considered for operative fixation when carrying out open reduction and internal fixation of fractures of the distal radius.